Development of Contextual-Based Narrative Text Module for Students of 7th Grade Junior High School - Shinta Larasati; Edi Suyanto; Siti Samhati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The problem in this study is related to the limitations of teaching materials in narrative text materials in schools. This study aims to produce, develop, and describe the feasibility of teaching material products in the form of "Narration Text Learning Modules (Fantasy Stories) Based on Contextual Approaches for Class VII Junior High School Students". The research method uses five of the ten steps in the research and development procedure according to Borg and Gall. The five steps of this research are 1) potential and problem analysis, 2) data collection, 3) product design, 4) design validation, and 5) product revision. Data collection techniques through observation, interviews, and distributing questionnaires in three schools. The results of this study are in the form of a Narrative Text Learning Module (Fantasy Story) based on a Contextual Approach for Class VII Junior High School Students. The Narrative Text Module Based on the Contextual Approach was declared feasible according to the researcher because all input, criticism, suggestions, and revisions from the validator had been followed up by the researcher. Revision of the module includes enlarging the less obvious view, adding contextual supporting images, and improving grammar. The results of the expert validation test obtained a score of 120 or with a percentage of 81.08% in the very feasible category. Based on the final condition of the module that the researcher has followed up, in the form of a revision of the validation results, it shows that the teaching material for the Narrative Text Module Based on Contextual Approach is suitable for use in teaching narrative texts for class VII SMP.